What are effective policies for promoting physical activity? A systematic review of reviews - Gelius, Peter; Messing, Sven; Goodwin, Lee; Schow, Diana; Abu-Omar, Karim (Preventive Medicine Reports, 2020)
The importance of policy for promoting physical activity (PA) is increasingly recognized by academics, and there is a push by national governments and international institutions for PA policy development and monitoring. However, our knowledge about which policies are actually effective to promote PA remains limited. This article summarizes the currently available evidence by reviewing existing reviews on the subject. Building on results from a previous scoping review on different types of PA-related evidence, we ran searches for combinations of the terms “physical activity”, “evidence”, “effect”, “review”, and “policy” in six different databases (PubMed, Scopus, SportDiscus, PsycInfo, ERIC, and IBSS). We used EPPI Reviewer 4 to further process the results and conduct an in-depth analysis. We identified 57 reviews providing evidence on 53 types of policies and seven broader groups of policies. Reviews fell into four main categories: 1) setting- and target group-specific; 2) urban design, environment and transport; 3) economic instruments; and 4) broad-range perspective. Results indicate that there is solid evidence for policy effectiveness in some areas (esp. school-based and infrastructural policies) but that the evidence in other areas is insufficient (esp. for economic policies). The available evidence provides some guidance for policy-makers regarding which policies can currently be recommended as effective. However, results also highlight some broader epistemological issues deriving from the current research. This includes the conflation of PA policies and PA interventions, the lack of appropriate tools for benchmarking individual policies, and the need to critically revisit research methodologies for collating evidence on policies.
CRIS-Team Scopus Importer:2020-04-28
Keywords: Effectiveness; Evidence; Health policy; Physical activity; Policy; Public health; Review